2016
DOI: 10.1016/j.brat.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Internet-delivered acceptance-based behaviour therapy for generalized anxiety disorder: A randomized controlled trial

Abstract: Generalized anxiety disorder (GAD) is a disabling condition which can be treated with cognitive behaviour therapy (CBT). The present study tested the effects of therapist-guided internet-delivered acceptance-based behaviour therapy on symptoms of GAD and quality of life. An audio CD with acceptance and mindfulness exercises and a separate workbook were also included in the treatment. Participants diagnosed with GAD (N = 103) were randomly allocated to immediate therapist-guided internet-delivered acceptance-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 51 publications
4
55
0
1
Order By: Relevance
“…Depression was examined by 11 studies, of which 5 included participants with a primary diagnosis of an anxiety disorder [ 36 , 56 - 59 ], 3 with a depressive disorder [ 37 , 53 , 54 ], 1 with both anxiety and depressive disorders [ 60 ], 1 with bipolar disorder [ 55 ], and 1 with bulimia disorder [ 61 ]. Usable data for meta-analysis of studies with a control group could be retrieved for 8 of these studies [ 36 , 37 , 53 , 54 , 56 , 59 - 61 ]. Johansson et al [ 60 ] reported data divided into two subgroups: those with a diagnosis of depression and those with a diagnosis of anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression was examined by 11 studies, of which 5 included participants with a primary diagnosis of an anxiety disorder [ 36 , 56 - 59 ], 3 with a depressive disorder [ 37 , 53 , 54 ], 1 with both anxiety and depressive disorders [ 60 ], 1 with bipolar disorder [ 55 ], and 1 with bulimia disorder [ 61 ]. Usable data for meta-analysis of studies with a control group could be retrieved for 8 of these studies [ 36 , 37 , 53 , 54 , 56 , 59 - 61 ]. Johansson et al [ 60 ] reported data divided into two subgroups: those with a diagnosis of depression and those with a diagnosis of anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Significant heterogeneity was noted ( Q =42.996, df =3, P <.001, I 2 =93.023, T 2 =0.974, T =0.987). We performed sensitivity analyses to examine the difference between studies including mindfulness-only therapies [ 36 , 37 ] and those including mindfulness integrative therapies [ 53 , 54 , 56 , 59 - 61 ]. Exploratory sensitivity analysis indicated that mindfulness integrative therapies had a significant effect on reducing depression while mindfulness-only therapies did not.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence supports the use of TBIs for prevention and treatment of other psychiatric disorders including, depression and anxiety, 4549 psychotic disorders, 50 and eating disorders. 51 The largest body of literature on TBIs for psychiatric disorders focuses on interventions for depression and anxiety (for review see 5254 ).…”
Section: Tbis For Other Psychiatric Disordersmentioning
confidence: 98%
“…While CBT has been the dominant model of therapy used in Internet interventions so far, different models have been and are being explored, including acceptance and commitment therapy, psychodynamic approaches, interpersonal psychotherapy, physical activity, mindfulness, and programs based on attention bias modification training.…”
Section: Treatment Approachmentioning
confidence: 99%